Weak Convergence Theorems on the Split Common Fixed Point Problem for Demicontractive Continuous Mappings - Huanhuan Cui; Luchuan Ceng; Fenghui Wang (Journal of Function Spaces)
We are concerned with the split common fixed point problem in Hilbert spaces. We propose a new method for solving this problem and establish a weak convergence theorem whenever the involved mappings are demicontractive and Lipschitz continuous. As an application, we also obtain a new method for solving the split equality problem in Hilbert spaces.